Craftworkers in Nineteenth Century Scotland Making and Adapting in an Industrial Age - Nenadic, Stana (Edinburgh University Press, 2021)
This book examines individuals, families and communities of craftworkers and their changing experience in town and country. Based on case studies drawn from personal, business, institutional and official records, as well as newspaper reports and visual illustrations, it looks at workplace dynamics and handmade wares shaped by personal consumption, rather than industrial production. Stana Nenadic examines the 'things' that were made and the values they embodied at a time when most Scots were still engaged in hand making - either for income or pleasure - despite Scotland's emergence as a great industrial powerhouse.